A Cointegration and Error Correction Modeling of Export Sector Performance in Kenya - Bunde , Aggrey Otieno (African Journal of Education,Science and Technology (AJEST), 2014)
Real exchange rate is an active source of discussions in Kenya. Whereas the export sector performance has improved since 2002, it continues to fall short of the ambitions of the vision 2030. In developing countries, misalignment in the exchange rate has often taken the form of overvaluation, which adversely affects the export sector. Overvaluation results in a real decline in the price of foreign goods relative to domestic goods. The general objective of this study was to investigate the behavior of exports in the presence of aid inflows and real exchange rate volatility in Kenya. The study hypothesized that exports do not respond positively to aid inflows and real exchange rate volatility. This study was guided by the trade theory and adopted Error Correction Model. Inferential statistics were applied using PC Give Ox-metrics, unit root, co integration and granger causality tests were done prior to estimation. The results confirms the dominant role played by economic prosperity of the export destination countries as demonstrated by the significant positive co-efficient of output growth of trading partners. Real exchange rate has a profound effect on export sector performance and the potential for export supply response is evident given by its positive co-efficient. The negative coefficient on the real exchange rate misalignment term highlights the adverse effect this has on export performance. A positive relationship is seen to exist as indicated by positive co-efficient of Aid in the model. The results of this study will be very important to macroeconomic policy analysts and researchers when designing policies that respond to macroeconomic challenges facing export sector performance in Kenya.